Olabiyi Babalola J. Yai (1939-2020): Philosopher, Polymath, Humanist - Sanya Osha (Yoruba Studies Review)
When Professor Abiola Francis Irele passed in 2017, we had met a couple of months earlier at a conference hosted by the Institute for Pan-African Thought and Conversation (IPTC) in Johannesburg. Throughout the huge conference, I had been beside Irele, ravenously tapping into his wealth of knowledge and experience, plying him with an endless barrage of questions relating to our intellectual history and the key figures who had indelibly marked and shaped its trajectory. The esteemed professor, ever so patient, was ready to respond to even the most uncomfortable of entreaties. He possessed the unflappable sangfroid of a sage yet there was nothing inaccessible about his almost earthy aura. He was unfailingly modest and never condescended to me even when he had ample reason to do so.